Ḥaz̤rat ʻUs̲mān G̲ẖanī : yaʻnī, Amīrulmūminīn Ḥaz̤rat ʻUs̲mān G̲ẖanī ke ʻahd-i ḵẖilāfat kī tārīḵẖ - Rafīq Bulandshahrī, Āg̲ẖā (SAMP early 20th-century Indian books project ;)
Short biography of ʻUthmān ibn ʻAffān, d. 656, Caliph of Islam.